Synthesis of n-butanol-rich C3+ alcohols by direct CO2 hydrogenation over a stable Cu–Co tandem catalyst - Irshad, Muhammad; Chun, Hee Joon; Khan, Muhammad Kashif; Jo, Heuntae; Kim, Seok Ki; Kim, Jaehoon (Applied Catalysis B: Environmental, 2024)
The direct conversion of CO2 into liquid fuels and chemical heterogeneous catalysts is considered a promising route to mitigate global warming issues. However, the production of n-butanol-rich C3+ alcohol from CO2 remains a significant challenge. Herein, we demonstrate that a Cu-rich bimetallic Cu–Co catalyst can achieve an unprecedentedly high space-time yield (STYC3+OH) of 80.8 mg g−1 h−1. The decoration of Co nanoparticles onto the dendritic Cu substrate established a crucial balance between CHx and CH3O* and regulated C–C coupling, which is a prerequisite for C3+ alcohol synthesis. We provide new mechanistic insights into n-butanol synthesis involving the C–O bond dissociation of an acetaldehyde intermediate on the interfacial Cu–Co site and subsequent C–C bond formation on the Cu site. Furthermore, the Cu–Co catalyst exhibited exceptional stability up to 1000 h by effectively suppressing re-oxidation and carbon deposition. The Cu–Co catalyst has great potential for large-scale CO2 hydrogenation to C3+ alcohol owing to its high selectivity and remarkable stability.
Keywords: A-stable; Bimetallics; C3 +alcohol; Catalyst stability; CO2 conversion; Cu-co catalysts; Direct conversion; Heterogeneous catalyst; N-butanol; ]+ catalyst; Butanol; C3 +alcohols; Catalyst stability; CO2 conversion; Cobalt; Copper